Proceedings of DINAME 2017 Selected Papers of the XVII International Symposium on Dynamic Problems of Mechanics - Fleury, Agenor de T.; Rade, Domingos A.; Kurka, Paulo R. G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the most significant contributions to the DINAME 2017 conference, covering a range of dynamic problems to provide insights into recent trends and advances in a broad variety of fields seldom found in other proceedings volumes. DINAME has been held every two years since 1986 and is internationally recognized as a central forum for discussing scientific achievements related to dynamic problems in mechanics. Unlike many other conferences, it employs a single-session format for the oral presentations of all papers, which limits the number of accepted papers to roughly 100 and makes the evaluation process extremely rigorous. The papers gathered here will be of interest to all researchers, graduate students and engineering professionals working in the fields of mechanical and mechatronics engineering and related areas around the globe.
Part 1: ROTORDYNAMICS -- Estimation of rotordynamic seal coefficients using active magnetic bearing excitation and force measurement -- Experimental estimation of equivalent damping coefficient of thrust bearings -- Analysis of the Dynamic Behavior of a Cracked Rotating Shaft by Using the Harmonic Balance Approach -- Part 2: VIBRATIONS AND STRUCTURAL DYNAMICS -- Tunable Auxiliary Mass Damper with Friction Joint: Numerical Assessment -- The Mechanical Behavior of Viscoelastic Materials in the Frequency Domain -- Curvature effects on vibrational power flow of smooth bent beams -- Nonlinear Identification Using Polynomial NARMAX Model and a Stability Analysis of an Aeroelastic System -- Dynamics of Helicopters with DVA under structural uncertainties -- Cable Dynamic Modeling and Applications in Three-Dimensional Space -- Optimization of the Fundamental Frequency of mechanical structures by using the bidirectional evolutionary structural method -- Operational Modal Parameters Identification Using the ARMAV Model -- Dynamic behavior and optimization of tow steered composite plates -- Evaluation of the dynamic response of buildings with TMDs under earthquakes -- Model based System testing approach for efficient testing of EPS systems -- Experimental assessments of the added mass of flexible cylinders in water: the role of modal shape representation -- Part 3: ROBOTICS AND MECHATRONIC SYSTEMS -- Dynamic modeling and simulation of a parallel planar manipulator with linear electric actuators using power flow approach -- Numerical and experimental analysis of a parallel 2 DOF manipulator -- Parameter optimization and active control of electromechanical suspension systems -- A neural network observer for injection rate estimation in common rail injectors with nozzle wear -- Lagrange's, Maggi's and Kane's equations applied to the dynamic modelling of serial manipulator -- Dynamic modelling of the manipulator of a mini hydraulic excavator -- Part 4: CONTROL OF MECHANICAL SYSTEMS -- Hardware-in-the-loop optimization of an interaction controller for improved coupled dynamics -- SDRE trajectory tracking control for a hovercraft autonomous vehicle -- Method for controlling stick-slip vibrations in slender drilling systems -- Control of multiple mobile robots in dynamic formations -- An application of Lurie problem in Hopfield neural networks -- Part 5: NONLINEAR DYNAMICS -- Rotations of the parametric pendulum excited by a reciprocating motion with a view on energy harvesting -- Part 6: VEHICLE DYNAMICS AND MULTIBODY SYSTEMS -- Analysis of control strategies for autonomous motorcycles stabilization and trajectories tracking -- Modelling and simulation of the rolling dynamics of a tractor-trailer truck vehicle -- Use of integrated control to enhance the safety of vehicles in run-off scenarios -- Yaw stability analysis of articulated vehicles using phase trajectory method -- The influence of inertial forces on manual wheelchair propulsion -- Numerical simulation of track settlement using a multibody dynamic software - A holistic approach -- Part 7: WAVE PROPAGATION, ACOUSTICS AND VIBROACOUSTICS -- Flexural wave band gaps in a 1D phononic crystal beam -- Investigating interface modes on periodic acoustic waveguides and elastic rods using spectral elements -- Measurement of the speed of leak noise propagation in buried water pipes: challenges and difficulties -- Passive control of noise propagation in tube systems using Bragg scattering -- Dynamic models for transmission lines and hoses -- Part 8: UNCERTAINTY QUANTIFICATION AND STOCHASTIC MECHANICS -- Assessment of uncertainties and parameter estimation in an offshore pipeline.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Control engineering; Robotics; Automation; Nonlinear Optics; Multibody Systems and Mechanical Vibrations; Control, Robotics, Automation; Nonlinear Optics